Kehidupan Sosial Ekonomi Petani Jagung Di Nagari Geragahan Kampung Tabuah Kecamatan Lubuk Basung Kabupaten Agam Tahun 2007-2020 - Nofriya Nofriya; Azmi Fitrisia (Jurnal Kronologi, 2022)
Abstract This study examines the socio-economic life of corn farmers in Nagari Geragahan, Tabuah Village, Lubuk Basung District, Agam Regency, 2007-2020. The problems are formulated as follows: "How is the development of corn production and distribution of corn in Nagari Geragahan, Kampung Tabuah in 2007-2020, How is the socio-economic life of corn farmers in Nagari Geragahan, Kampung Tabuah in 2007-2020". This study aims to determine the socio-economic life of corn farmers in Nagari Geragahan, Tabuah Village in 2007-2020 and to determine the economic impact of the community in 2007-2020. This research is included in historical research with the following research methods: (1) Heuristics is an activity to collect or find sources of information related to the problem, which consists of primary sources and secondary sources. Primary sources can be obtained through oral sources, namely informants consisting of community leaders, corn farmers, while written sources are in the form of archives and documents relevant to the research study. In addition, an observation method was also carried out, namely by conducting field observations by looking at the description of the socio-economic life of corn farmers. (2) Source Criticism consists of internal criticism and external criticism, namely by testing the authenticity and authenticity of the information, and the author has compared it with different sources. (3) Interpretation, namely interpreting and connecting with existing facts. (4) Presentation of research results in the form of Thesis. Based on the results of the study, it shows that the socio-economic life of corn farmers has experienced significant development since 2007-2017, this is evidenced by the greatly increased corn production from 2007-2017. However, starting from 2018-2020 corn production began to decline, this was caused by: (1) many farmers used land to plant corn which was divided into 2, for example some for planting rice and part for planting corn. (2) The price of corn is 4,000 – 3,000 per kilogram. (3) the growth of corn is not good. (4) the price of corn that cannot be determined every month. Keywords: Socio-Economic, Corn Farmers, Nagari Geragahan Kampung Tabuah